2011
DOI: 10.3167/jemms.2011.030209
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Remember Slavery

Abstract: Drawing on the fields of education, memory, and cultural studies, this article argues that as important cultural memory products, government-sponsored museum education initiatives require the same attention that history textbooks receive. It investigates the performance of recent shifts in historical consciousness in the context of museum field trip sessions developed in England in tandem with the 2007 bicentenary of the abolition of the slave trade. Analysis of fieldwork data is presented in order to illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Museum educators played central roles, but actively involved students as well through methods such as guided questioning, immersive sensory experiences, role plays or dress-ups. Other studies also observed combinations, most frequently socratic questioning methods and (sometimes informal) bidirectional interactions between learner and instructor (Ferrer-Fons & Rovira-Martínez, 2021;Spalding, 2011;Trofanenko, 2006Trofanenko, , 2014Uppin & Timoštšuk 2019;Wallace-Casey, 2016). Tigert et al (2021) added to this observation that the occurrence of learner-instructor interaction and learners' active participation in the instructional discourse was rather triggered if the instructor mainly used open questions, possibly preceded by closed questions as a 'lead-in' activity.…”
Section: Category 2 Instructional Methods: Between Student-and Teache...mentioning
confidence: 95%
See 3 more Smart Citations
“…Museum educators played central roles, but actively involved students as well through methods such as guided questioning, immersive sensory experiences, role plays or dress-ups. Other studies also observed combinations, most frequently socratic questioning methods and (sometimes informal) bidirectional interactions between learner and instructor (Ferrer-Fons & Rovira-Martínez, 2021;Spalding, 2011;Trofanenko, 2006Trofanenko, , 2014Uppin & Timoštšuk 2019;Wallace-Casey, 2016). Tigert et al (2021) added to this observation that the occurrence of learner-instructor interaction and learners' active participation in the instructional discourse was rather triggered if the instructor mainly used open questions, possibly preceded by closed questions as a 'lead-in' activity.…”
Section: Category 2 Instructional Methods: Between Student-and Teache...mentioning
confidence: 95%
“…Harker and Badger (2015) and McCully, Weiglhofer and Bates (2021) examined the design of an exhibition and how its educational resources created learning opportunities, contextualising these through interviews with teachers and museum educators. Regarding the enactment of physical instruction, several studies observed learning sessions led by museum educators (Keenan, 2019;Savenije & de Bruijn, 2017), experienced teachers (Trofanenko, 2006(Trofanenko, , 2014 or by both together (Ferrer-Fons & Rovira-Martínez, 2021;Spalding, 2011;Wallace-Casey, 2016).…”
Section: Category 2: Focus On the Relationship Between Instructional ...mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the emotional experiences that accompany visits to such sites can hinder students' learning; however, the interplay between the cognitive, affective and physical dimensions of students' historical experiences in authentic learning contexts has not been explored fully yet (Flennegård and Mattsson, 2021;Nesfield, 2015). In research investigating visits to museums and historical sites, as well as the role that these sites play in teaching, questions about students' varying historical experiences are featured more prominently (see Marcus, 2007;Rohlf, 2015;Savenije et al, 2014;Spalding, 2011). It has been noted that the character of the narratives that students encounter during these visits is important, particularly the extent to which the narratives are either 'open' or 'closed'; that is, the extent to which they give students the opportunity to relate to them.…”
Section: Previous Researchmentioning
confidence: 99%